Salmonella Gallinarum multirresistentes e formadoras de biofilmes em cascas de ovos são sensíveis a bacteriófagos - Rizzo, Natalie Nadin (2017)
The fowl typhoid has great economic importance due to the high costs with control programs, due to the sanitary sacrifice of the birds and discard of the eggs in the hatcheries. Salmonella Gallinarum, a few decades ago, had been considered to be eradicated in commercial birds in Brazil. However, due to the lack of controls, such as biosecurity, inputs, monitoring and health programs, associated with the virulence mechanisms of the pathogen, this disease has been reemerging in recent years. S. Gallinarum causes infection and clinical manifestations, with high bacterial concentration in the tissues and can be transmitted vertically and horizontally. The contamination via transovarian renders the eggs unviable for the production of birds, which can become asymptomatic carriers and transmit the pathogen soon after the birth. Transmission of the microorganism horizontally can be characterized by contaminating the eggs through the bark soon after laying, in the nests or beds of aviaries. Virulence factors influence the treatments with antimicrobial drugs and environmental control with the use of disinfectants. It is of fundamental importance the study of these factors to assist in the epidemiological analysis of the outbreaks occurred and, also, to establish strategies of new controls. The objective of this study was to characterize the phenotypic and genotypic characteristics of different S. Gallinarum isolates from agroindustry production through the evaluation of antimicrobial susceptibility and disinfectant, bacteriophage lysis potential, virulence genes, biofilm formation Polystyrene and eggshells. It can be observed that the S.Gallinarum are multiresistant to the antimicrobials, sensitive to the bacteriophages tested, and potentially virulent, according to the genetic profiles obtained. Most of the isolates formed biofilm in polystyrene at 22°C and 42°C, with no statistical difference (p = 0.0965) between the temperatures tested. There was a higher biofilm formation in eggshells at 22°C (4,656 log10UFC / cm2), with a statistical difference when compared to biofilms formed at 36°C and 42°C. The action of the commercial disinfectant, in the concentration 1.5% and time 5 minutes, promoted the removal of the biofilm, statistically significant, only in the formation at 22°C, leading to a reduction of 3,125 log10. The presence of virulence genes, the multiresistance and the ability to form biofilms on different surfaces and temperatures by S. Gallinarum studied, isolated from commercial birds, makes us suppose that these can be relevant factors for the SG to remain present in poultry farms and is involved in intermittent outbreaks. Despite the worrying scenario, the possibility of biological control of SG by bacteriophages brings us a promising alternative for the containment of this microorganism.